Effects of night break light sources on morphology and pigment content in standard chrysanthemum (Chrysanthemum morifolium) - Ranjit Singh; Dhawan Shweta Macchindra; Madhu Bala (Current Horticulture, 2025)
This study investigated the effects of incandescent bulbs, compact fluorescent lamps (CFL), and light-emitting diodes (LED) on morphological and pigment traits of ten Chrysanthemum morifolium varieties. Using a factorial completely randomized design with three replications, we measured plant height, leaf area index (LAI), flowering time, duration, and pigment content. LED lighting produced the tallest plants (103.35 cm), highest LAI (6.28), and largest flowers (19.58 cm). It also yielded the highest anthocyanin (1.84 mg/g) and carotenoid (96.12 mg/g) levels. Incandescent lighting induced earliest flowering (158.87 days), while LED extended flowering duration to 36.34 days. Results demonstrate significant influence of night break light sources on C. morifolium growth, flowering, and pigment synthesis, with LEDs showing the greatest overall benefit.